Determinants of Organizational Citizenship Behavior of West Sumatra Regional Police ASN through Organizational Commitment - Haniva Dela Gusta; Muhammad Oceano Fauzan (CAKRAWALA : Management Science Journal, 2026)
This study examines the effects of Job Satisfaction, Perceived Organizational Support (POS), and Person–Job Fit on Organizational Citizenship Behavior (OCB), with Organizational Commitment serving as a mediating variable among Civil Servants (ASN) of the West Sumatra Regional Police. Grounded in Social Exchange Theory and Organizational Support Theory, the research employed a quantitative approach using a survey of 182 ASN respondents selected through proportionate random sampling. Data were analyzed using Structural Equation Modeling (SEM-PLS). The findings indicate that Job Satisfaction, Perceived Organizational Support, Person–Job Fit, and Organizational Commitment significantly influence Organizational Citizenship Behavior. Furthermore, Job Satisfaction, Perceived Organizational Support, and Person-Job Fit significantly enhance Organizational Commitment. The mediation analysis confirms that Organizational Commitment partially mediates the relationships between the three antecedent variables and Organizational Citizenship Behavior. These results suggest that strengthening organizational support, improving employee–job compatibility, and enhancing job satisfaction can foster stronger commitment and encourage employees to engage in discretionary behaviors that contribute to organizational effectiveness and public service performance.